1990
DOI: 10.1111/j.1439-0418.1990.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some olfactory and optical properties of fruits on host location by the Mediterranean fruit fly (Cera titis capita ta Wied.)

Abstract: Host location by the Mediterranean fruit fly (Cerutitis cupitatu Wiedemann) was studied from the viewpoint of olfactory and optical properties of certain fruits. Oranges, tangerines, plums, lemons, strawberries and grapes were found to be significantly more attractive for mated females than for mated males of C. cupitutu ( fig. 1). When compared with mated females, virgin females were definitely less attracted to oranges and odourless orange dummies (fi . 2). Dimension has a clearcut influence on the attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…For example, electrophysiological recordings from antennae of medfly adults have shown a higher sensitivity of females than males for some Citrus peel oils and volatile compounds (Light et al 1988(Light et al , 1992Levinson et al 1990;Hernandez et al 1996), while behavioral tests revealed a stronger preference of males than females for the volatiles of orange flavedo (Katsoyannos et al 1997). In females, odor preference may be affected by mating behavior: it has been observed that females are more attracted by the male-produced pheromone than the ripe guava odor during early sexual maturity, but this preference is inverted after mating (Jang 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example, electrophysiological recordings from antennae of medfly adults have shown a higher sensitivity of females than males for some Citrus peel oils and volatile compounds (Light et al 1988(Light et al , 1992Levinson et al 1990;Hernandez et al 1996), while behavioral tests revealed a stronger preference of males than females for the volatiles of orange flavedo (Katsoyannos et al 1997). In females, odor preference may be affected by mating behavior: it has been observed that females are more attracted by the male-produced pheromone than the ripe guava odor during early sexual maturity, but this preference is inverted after mating (Jang 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found possible female attractants among plant, fruit, or protein hydrolysate volatiles. Many of these compounds produce electroantennogram responses from female antennae or attract C. capitata females in laboratory tests (Keiser et al 1975;Light et al 1988Light et al , 1992Jang et al 1989;Dickens et al 1990; Levinson et al 1990;Cossé et al 1995;Hernández et al 1996;Prokopy and Vargas 1996;Warthen et al 1997). However, Þeld attractiveness or effectiveness has only been investigated under varied experimental conditions for a few compounds such as (E)-6-methyl nonenoate, (E)-6-nonenol and aliphatic acids (Ohinata et al 1977), ammonia salts (Gothilf andLevin 1987, Baker et al 1990), alkyl-pyrazines and geranyl acetate (Baker et al 1990), protein hydrolysates (Gothilf and Levin 1987, Heath et al 1994, Katsoyannos and Hendrichs 1995, and ammonia compounds with methylamines and putrescine (Heath et al 1991(Heath et al , 1994(Heath et al , 1996Epsky et al 1995;Ros et al 1997;Bakri et al 1998).…”
mentioning
confidence: 99%
“…Total airborne volatiles from fresh oranges elicited greater response of females than males (Levinson 1990;Hernández et al 1996). Additional tests conducted in large field cages housing naturally planted orange trees showed that both sexes of C. capitata respond to chemicals released from artificial cuts made in the pulp of peeled oranges (Citrus sinensis L.) and also to natural or commercial orange juice applied to the surface of yellow 7.0 cm diameter spheres (Katsoyannos et al 1997).…”
Section: Genus Ceratitismentioning
confidence: 96%
“…EAGs or electrophysiological recordings from olfactory sensilla on the antennal funiculi of C. capitata showed that both males and females detect blends of citrus peel essential oils (Levinson 1990;Hernández et al 1996) as well as most individual compounds (Light et al 1992;Hernández et al 1996). Total airborne volatiles from fresh oranges elicited greater response of females than males (Levinson 1990;Hernández et al 1996).…”
Section: Genus Ceratitismentioning
confidence: 99%